Blood Brain–Barrier Disruption of Nonionic Iodinated Contrast Medium Following Coil Embolization of a Ruptured Intracerebral Aneurysm - Uchiyama, Yusuke; Abe, Toshi; Hirohata, Masaru; Tanaka, Norimitsu; Kojima, Kazuyuki; Nishimura, Hiroshi; Norbash, Alexander M.; Hayabuchi, Naofumi (American Journal of Neuroradiology, 2004)
Summary: Few reports of temporary disruption of the blood-brain barrier (BBB) following neurointerventional procedures, presumably caused by nonionic radiographic contrast medium (CM), exist in the literature. We described such a case in a 72-year-old man presenting with acute subarachnoid hemorrhage, who underwent coil embolization of a ruptured anterior communicating artery complex aneurysm. At the time of his follow-up CT examination, a large amount of iodine was found in the cerebrospinal fluid (CSF). Because of this experience, the iodine concentration in the CSF of five other patients who also underwent an intracranial endovascular procedure was measured. It was concluded that this increased iodine might have been caused by temporary leakage or breakdown of the BBB. Even if the total amount of CM may not be excessive, the disproportionately high concentration injected into a single vascular territory may pose a unique set of variables increasing the risk of BBB disruption.